Pendampingan Penerapan IoT untuk Monitoring dan Kontrol Listrik untuk Petani Hidroganik Desa Kanigoro Malang - Darto Darto; Agus Suprapto; Wahyu Dirgantara (University of Merdeka Malang, 2021)
The farming profession in the industrial era 4.0 is considered ancient and has no potential and bonafide. To change such a mindset, Community Service (PKM-Unmer Building Village) in collaboration with hydroganic farmer groups to make greenhouse and hydro-gas models accompanied by water flow monitoring (flow sensor), temperature, and humidity monitoring (DHT11 sensor) and electricity control (UPS). By utilizing the IoT concept in a monitoring tool that is placed in hydroganics, it can monitor the flow of water and plants in real-time. To access monitoring, the cellphone must be connected to the same wifi as the device, then enter the IP address using a mobile browser. The method of implementation used consists of three stages: preparation includes a review of partner locations, coordination, and the number of partners and existing facilities, pilot and, socialization. The results obtained from this activity are to accelerate and make it easier to control the hydroganics contained in the greenhouse in real-time. By utilizing a UPS to make the water pump always on, the equipment is not easily damaged if there is an electrical disturbance such as a blackout or short circuit. PKM-Unmer Building Village produces a pilot modeled in a greenhouse, socialization to the community and Bengkel Mimpi farmer groups, and training to make simple monitoring tools.